IL-17: Balancing Protective Immunity and Pathogenesis - Lu Sun; Lufei Wang; Bethany B. Moore; Shaoping Zhang; Peng Xiao; Ann M. Decker; Hom-Lay Wang (Journal of Immunology Research)
The biological role of interleukin 17 (IL-17) has been explored during recent decades and identified as a pivotal player in coordinating innate and adaptive immune responses. Notably, IL-17 functions as a double-edged sword with both destructive and protective immunological roles. While substantial progress has implicated unrestrained IL-17 in a variety of infectious diseases or autoimmune conditions, IL-17 plays an important role in protecting the host against pathogens and maintaining physiological homeostasis. In this review, we describe canonical IL-17 signaling mechanisms promoting neutrophils recruitment, antimicrobial peptide production, and maintaining the epithelium barrier integrity, as well as some noncanonical mechanisms involving IL-17 that elicit protective immunity.